Determinants of Pneumonia in Toddlers: Multivariate Analysis - Sari Suriani; Rizka Choirunnisa (Gema Lingkungan Kesehatan, 2026)
Pneumonia remains a leading cause of morbidity and mortality among toddlers aged 12-59 months at Cikande Health Center Serang Regency, with 89 cases reported from January to March 2025. This unmatched case-control study included 118 toddlers (59 pneumonia cases and 59 healthy controls from nearby households, 1:1 ratio, purposive sampling). Pneumonia was defined as cough ≥2 days with rapid breathing or chest indrawing. Data on toddler gender, maternal education/knowledge, bedroom ventilation (≥10% floor area), humidity (40-60% RH), occupancy density (≤2 persons/room) and cigarette smoke exposure were analyzed via Chi-Square (bivariate) and multiple logistic regression (multivariate, stepwise elimination, interaction tests) using SPSS. Bivariate analysis showed significant associations (p < 0.05) for all factors. Multivariate modelling retained maternal education (pv=0.041, OR=2.606, 95% CI: 1.042-6.518), maternal knowledge (pv=0.003, OR=3.916, 95% CI: 1.580-9.708), bedroom ventilation (pv=0.026, OR=2.771, 95% CI: 1.126-6.818), bedroom humidity (pv=0.001, OR=5.360, 95% CI: 2.077-13.835) and occupancy density (pv=0.006, OR=3.676, 95% CI: 1.464-9.228). Bedroom humidity was the most dominant factor. No significant interactions found. Modifiable environmental factors (humidity, density) and maternal factors are key pneumonia determinants. Interventions should target home environmental improvements and maternal education.